THE EFFECT OF LEVERAGE, PROFITABILITY, AND FIRM SIZE ON TAX AVOIDANCE ON MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Maya Safira Dewi; Muhammad Haryadi Thareq (PT. Berkah Digital Teknologi, 2025)
Purpose: To analyze the effect of leverage, profitability, and firm size on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. Research Methodology: Purposive sampling method; secondary data from idnfinancials.com and idx.co.id; data covering 2017-2019. Results: Leverage positively influences tax avoidance; profitability and firm size do not influence tax avoidance. Limitations: The study is limited to manufacturing companies listed on the Indonesia Stock Exchange over a specific three-year period. Contribution: Useful for researchers and practitioners in the fields of finance, taxation, and corporate governance.